(untitled) (Acta Entomológica Chilena, 2022)
Through the study of exuviae, the last instar larva and some characters of the pupa of Polymerius chilensis (Laporte, 1834) (Coleóptera: Dascilloidea: Rhipiceridae) are described. The larva has a three segmented antenna, a subantennal protuberance, maxillary cardines well developed, three segmented maxillary palpi, two segmented labial palpi, one seta on tarsungulus and lacks urogomphi and the eighth pair of abdominal spiraculae. The pupa is characterized by dorsal and ventral tubercles of the ninth abdominal segment and a marginal ridge in the seventh abdominal ventrite. The exuviae were found within a subterranean chamber together with a female imago of Polymerius chilensis and a cicada nymph remains, verifying the parasitic condition of the larvae of Rhipiceridae.